Efektifitas Praktik Penegakan Hukum Perkara Tindak Pidana Korupsi Pasca Putusan Mahkamah Konstitusi Nomor 25/PUU-XIV/2016 - Imanuel Jerry Arthur Lawalata; Jessyca Haniel Picauly (CV. ULIL ALBAB CORP, 2024)
The purpose of this writing is to discuss the Post Constitutional Court Decision Number 25/PUU-XIV/2016 removed the word